Edukasi Kesehatan Pendengaran Akibat Penggunaan Headset atau Earphone di Poliklinik THT RSUD Praya - Eka Arie Yuliyani; Ika Prasetyaningrum; Ni Made Utami Wulandari; M. Andre Darmawan (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Ear and hearing health are often neglected, and sometimes people are unaware of hearing loss. Hearing loss can be caused by various factors and can affect all age groups. Noise is one factor that causes hearing loss. Improper use of headsets or headphones can cause hearing loss called Noise-Induced Hearing Loss (NIHL). Hearing loss in NIHL is a sensorineural type that generally affects both ears. This educational activity was conducted with the aim of providing information to the public about the importance of maintaining ear and hearing health and how to prevent it. Participants were very enthusiastic about participating in the activity and listening to every piece of information presented. The high level of enthusiasm from the participants can be used as a benchmark and evaluation of activities for better implementation in the future